Assessment of anxiety in children during the COVID‐19 pandemic - Carlos Lastra; Robert Abrahams; Gregory Anash; Kyle Prisby; Luz Goyco‐Ortiz; Andrea Melean; Rosanne Moreno; Alexander Schramm (Wiley, 2024)
Abstract Objective This study assessed anxiety levels in children during the COVID‐19 pandemic and explored how factors related to COVID‐19 may have affected the prevalence of anxiety disorders among the pediatric population. Methods Childhood anxiety symptoms were assessed at various pediatric practices in Central New Jersey between July 2021 and September 2022. The sample comprised 476 children and adolescents aged 8-17 who participated in the Screen for Child Anxiety Related Disorders (SCARED) questionnaire, administered at their annual well‐child visits. Participants included both the child and the caregiver. The anxiety prevalence was compared with prepandemic standards published by the Centers for Disease Control (CDC). Results The prevalence of anxiety for children aged 8-17 years (28.3%) was greater than prepandemic levels (7.1%; p < 0.0001). Among children aged 8-11, anxiety increased from 6.6% to 38.1% (p < 0.0001), while for children aged 11-17, anxiety increased from 10.5% to 22.2% (p < 0.0001). Previously diagnosed anxiety was a strong predictor of a high anxiety score on the questionnaire (mean = 28.95) compared with children without a history of anxiety (mean = 17.65; p < 0.001). Furthermore, a disparity was identified in the responses between the child and the caregiver questionnaires (p < 0.0001). Conclusion This study shows that children's anxiety levels increased during the COVID‐19 pandemic. Moreover, an inconsistency was found between children self‐reporting anxiety and caregivers underreporting their child's anxiety. These findings underscore the need for targeted support for those affected, especially children with a history of anxiety.